(untitled) - Blyth, Thomas Scott (London, 2005)
This book provides a lucid and concise introduction to the basic results concerning the notion of an order. Although it is mainly intended for beginning postgraduates, the prerequisities are minimal and selected parts can profitably be used to broaden the horizon of the advanced undergraduate.
Keywords: Ordered algebraic structures,Lattice theory,Lưới,Cấu trúc đại số